(untitled) (Conferencea, 2023)
This article is about the formation of the archive system in the Surkhan oasis written about. First of all, in this regard, it should be noted that the collection of such a huge volume of documents is a positive result of years of dedicated work and the consistent completion of various stages of archival work in our country. Naturally, in these unique processes, the creation of the state archive, the creation of a work system in the field, the establishment of new procedures, the development of specific rules at the level of the requirements of the time, and the training of specialist personnel who can work in modern archives were carried out.